2002
DOI: 10.1590/s0100-84042002000200010
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização morfo-anatômica da folha e do caule de Brachiaria brizantha (Hochst. ex A. Rich.) Stapf e B. humidicola (Rendle) Schweick. (Poaceae)

Abstract: -(Leaf and stem morpho-anatomical characterization of Brachiaria brizantha (Hochst. ex A. Rich.) Stapf and B. humidicola (Rendle) Schweick. (Poaceae)). The morpho-anatomy of the leaf and stem of B. brizantha and B. humidicola were studied at three plant stratums. The difference among the species and the different stratums were investigated in order to justify the different intensities of consumption that occurs with plant aging. The experiment was carried out in a greenhouse and on plants cultivated in plastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…Alves de Brito et al (1999) found that lignified tissues, in leaves and stems, can increase according to plant growth. Moreover, cultivars from the same species can have different lignin increments (Akin, 1989;Silva-Lima et al, 2001a,b;Brito and Rodella, 2002). Our diploid type showed different lignin content and different cell wall thickness, while the tetraploid sample had a thicker cell wall.…”
Section: Discussionmentioning
confidence: 58%
“…Alves de Brito et al (1999) found that lignified tissues, in leaves and stems, can increase according to plant growth. Moreover, cultivars from the same species can have different lignin increments (Akin, 1989;Silva-Lima et al, 2001a,b;Brito and Rodella, 2002). Our diploid type showed different lignin content and different cell wall thickness, while the tetraploid sample had a thicker cell wall.…”
Section: Discussionmentioning
confidence: 58%
“…This characteristic is common in tropical grasses and may increase as a result of the adaptation to the environment, for being responsible for the winding and unwinding of the leaf in warm periods, avoiding the loss of water (Paciullo et al, 2002). The mesophyll was homogeneous, as described by Brito and Rodella (2002) to C4 grasses. It was verified the occurrence of a similar anatomical organization among the representatives of the three genera analyzed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…As células buliformes apresentaram paredes mais delgadas que as demais células epidérmicas, provavelmente composição química diferente, característica esta, confirmada pela dupla coloração (azul de astra + fucsina básica) utilizada por Brito & Rodella (2002). Nicolau et al (2010) caracterizaram estas células como motoras, sendo responsáveis pelo enrolamento e/ou dobramento das folhas em condições ambientais adversas.…”
Section: Resultsunclassified
“…Brito & Rodella (2002), verificaram que U. brizantha apresentou 5 camadas de células de parênquima de preenchimento na região de quilha, quantidade também visualizada no presente trabalho em plantas que não aparentaram acometimento a SMP (Fig. 14).…”
Section: Resultsunclassified